The N-terminal cytoplasmic region of NCBE displays features of an intrinsic disordered structure and represents a novel target for specific drug screening - Bjerregaard-Andersen, Kaare; Perdreau-Dahl, Harmonie; Guldsten, Hanne; Praetorius, Jeppe; Jensen, Jan K.; Morth, Jens Preben (Frontiers in Physiology, 2013)
The sodium dependent bicarbonate transporter NCBE/NBCn2 is predominantly expressed in the central nervous system (CNS). The highest protein abundance is found in the choroid plexus. The primary function of this integral plasma membrane transport protein is to regulate intracellular neuronal pH and probably to maintain the pH homeostasis across the blood-cerebrospinal fluid barrier (CSFB). NCBE has a transmembrane region consisting of 10 predicted α-helices. The N- and C- termini are both cytoplasmic, with a large N-terminal domain (Nt-NCBE) and a relatively small C-terminal domain (Ct-NCBE). The cytoplasmic N-terminal domain is likely involved in bicarbonate recognition and transport and contains key areas of regulation through pH sensing and protein - protein interactions (PPIs). Intrinsic disordered proteins (IDPs) and regions (IDPRs) are defined as not having any rigid three-dimensional structure under physiological conditions and are believed to be involved in signaling networks in which specific, though with low affinity, PPIs play an important role in the signaling event. We show that NCBE and other SLC4 family members have a high level of predicted intrinsic disorder prevalent in the cytoplasmic regions. To provide biophysical evidence for the IDPR predicted in Nt-NCBE, we isolated recombinant NCBE from E. coli and purified it to >99 % purity and used it to perform differential scanning fluorescence spectroscopy (DSF), in the search for small molecules that induce secondary or tertiary structure. This will promote the current need to develop selective drugs for individual SLC4 family members. We have also determined a low resolution X-ray crystal structure of the N-terminal core domain at 4.0 Å resolution. The N-terminal cytoplasmic domain of AE1 (cdb3) shares a similar fold with the N-terminal core domain of NCBE. The crystal conditions for the full-length N-terminal domain have been explored, however, only the core domain forms diffracting crystals.